Pedunculopontine Nucleus Stimulation: Where are We Now and What Needs to be Done to Move the Field Forward? - Morita, Hokuto; Hass, Chris J.; Moro, Elena; Sudhyadhom, Atchar; Kumar, Rajeev; Okun, Michael S. (Frontiers in Neurology, 2014)
Falls and gait impairment in Parkinson’s Disease (PD) is a leading cause of morbidity and mortality, significantly impacting quality of life and contributing heavily to disability. Thus far, postural instability and gait freezing have been refractory to current treatment approaches and remains a critical unmet need. There has been increased excitement surrounding the surgical targeting of the pedunculopontine nucleus (PPN) for addressing axial symptoms in PD. The PPN and cuneate nucleus comprise the mesencephalic locomotor region and electrophysiologic studies in animal models and human imaging studies have revealed a key role for the PPN in gait and postural control, underscoring a potential role for DBS surgery. Previous limited studies of PPN deep brain stimulation (DBS) in treating gait symptoms have had mixed clinical outcomes, likely reflect targeting variability and the inherent challenges of targeting a small brainstem structure that is both anatomically and neurochemically heterogeneous. Diffusion tractography shows promise for more accurate targeting and standardization of results. Due to the limited experience with PPN DBS, several unresolved questions remain about targeting and programming. At present, it is unclear if there is incremental benefit with bilateral vs unilateral targeting of PPN or whether PPN targeting should be performed as an adjunct to one of the more traditional targets. The PPN also modulates nonmotor functions including REM sleep, cognition, attention, arousal, and these observations will require long term monitoring of to fully characterize potential side effects and benefits. Surgical targeting of the PPN is feasible and shows promise for addressing axial symptoms in PD but may require further refinements in targeting, improved imaging, and better lead design to fully realize benefits. This review summarizes the current knowledge of PPN as a DBS target and areas that need to be addressed to advance the field.